2010
DOI: 10.1242/jcs.055103
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of protein-sorting machineries at the trans-Golgi network in Drosophila melanogaster

Abstract: SummaryTargeting of proteins to their final destination is a prerequisite for living cells to maintain their homeostasis. Clathrin functions as a coat that forms transport carriers called clathrin-coated vesicles (CCVs) at the plasma membrane and post-Golgi compartments. In this study, we established an experimental system using Schneider S2 cells derived from the fruit fly, Drosophila melanogaster, as a model system to study the physiological roles of clathrin adaptors, and to dissect the processes of CCV for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
29
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 51 publications
8
29
0
Order By: Relevance
“…Anti-Rg staining also displayed a granular pattern reminiscent of the Golgi network (Fig. 1 I), a cellular structure that is dispersed throughout the cell in fruit flies (Kametaka et al, 2010). Using the cis-Golgi marker GM130, we demonstrated that Drosophila Rg resides near or within the Golgi complex (Fig.…”
Section: Resultsmentioning
confidence: 79%
“…Anti-Rg staining also displayed a granular pattern reminiscent of the Golgi network (Fig. 1 I), a cellular structure that is dispersed throughout the cell in fruit flies (Kametaka et al, 2010). Using the cis-Golgi marker GM130, we demonstrated that Drosophila Rg resides near or within the Golgi complex (Fig.…”
Section: Resultsmentioning
confidence: 79%
“…Indeed, partial loss-of-function AP-1 mutants exhibit small granules similar to those found in PI4KII mutants (Burgess et al, 2011). Alternatively, PI4KII might affect the Golgi recruitment of other PI4P-binding proteins involved in post-Golgi vesicular trafficking, for example GGA or GOLPH3 (Dippold et al, 2009;Hirst et al, 2009;Kametaka et al, 2010). Nonetheless, the overwhelming majority of Sgs3 appears to traffic normally to small secretory granules, indicating that post-Golgi trafficking of glue cargo proteins is relatively unaffected in PI4KII mutants.…”
Section: Discussionmentioning
confidence: 90%
“…Mutating the L 339 L 340 motif in the ␤ 2 AR did not change ligand binding, G protein coupling, or signaling to adenylate cyclase (36), indicating that decreased anterograde trafficking of the F(X) 6 AA mutant receptor was not caused by improper receptor folding. Clathrin-associated proteins such as the heterotetrameric adaptor protein (AP) complexes and the monomeric Golgi-localized, ␥-adaptin ear-containing, ARF-binding proteins (GGAs) function as "adaptors," promoting both concentration of cargo and recruitment of clathrin at sites of transport-carrier formation (40). AP-1 and GGAs, in particular, localize to the TGN and endosomes and participate in protein trafficking between these two compartments (40 -42).…”
Section: Discussionmentioning
confidence: 99%